The Effects of Natural Weathering on the Mechanical and Thermal Properties of rPP/MAH-g-PP/Bamboo Textile Waste Composites - Ahmad Fareez Zulhaqeem,; Ahmad, Mazatusziha; Abdul Haq, Reazul Haq (Progress in Engineering Application and Technology, 2026)
The increasing amount of plastic and textile waste has intensified the need for sustainable composite materials made from recycled sources. The study investigates the natural weathering effects on the mechanical and thermal properties of MAPP-compatibilized bamboo textile waste-reinforced recycled polypropylene composites. The objectives were to characterize alkali-treated bamboo textile waste fibers and to evaluate the mechanical and thermal properties of MAPP-compatibilized bamboo textile waste-reinforced recycled polypropylene composites. Alkali treatment was conducted using NaOH to modify fiber surfaces followed by composite fabrication through internal mixing and compression molding with fiber loadings of 5, 15, and 25 wt%. Characterization of fibers was carried out using FTIR and SEM. Mechanical properties were tested through tensile testing on Young’s modulus, tensile strength, and elongation at break while thermal behavior was tested using thermogravimetry analysis and differential scanning calorimetry. Natural weathering exposure was conducted for 7 days. Results showed that alkali treatment effectively removed surface impurities and increased roughness of fiber surface, enhancing the fiber-matrix interaction. Unweathered composites showed better tensile properties with increasing fiber loadings while weathered composites were weaker due to photo-oxidative degradation and moisture ingress. TGA analysis shows reduction in initial degradation temperature and peak decomposition temperature for weathered composites, while DSC analysis indicated reduced melting enthalpy and increasing crystallinity. The composite containing 15 wt% fiber loading exhibited the best balance between performance and practicality of use compared to the composite containing 5 and 15 wt%. It can be concluded that natural weathering adversely effects the mechanical and thermal properties of bamboo textile waste-reinforced recycled polypropylene for long-term performance, highlighting the need for further stabilization for outdoor applications.